The extrafollicular response is sufficient to drive initiation of autoimmunity and early disease hallmarks of lupus - Voss, Lasse F.; Howarth, Amanda J.; Wittenborn, Thomas R.; Hummelgaard, Sandra; Juul-Madsen, Kristian; Kastberg, Kristian S.; Pedersen, Mathias K.; Jensen, Lisbeth; Papanastasiou, Anastasios D.; Vorup-Jensen, Thomas; Weyer, Kathrin; Degn, Søren E. (Frontiers in Immunology, 2022)
Many autoimmune diseases are characterized by germinal center (GC)-derived, affinity-matured, class-switched autoantibodies, and strategies to block GC formation and progression are currently being explored clinically. However, extrafollicular responses can also play a role. The aim of this study was to investigate the contribution of the extrafollicular pathway to autoimmune disease development. We blocked the GC pathway by knocking out the transcription factor Bcl-6 in GC B cells, leaving the extrafollicular pathway intact. We tested the impact of this intervention in two murine models of systemic lupus erythematosus (SLE): a pharmacological model based on chronic epicutaneous application of the Toll-like receptor (TLR)-7 agonist Resiquimod (R848), and 564Igi autoreactive B cell receptor knock-in mice. The B cell intrinsic effects were further investigated in vitro and in autoreactive mixed bone marrow chimeras. GC block failed to curb autoimmune progression in the R848 model based on anti-dsDNA and plasma cell output, superoligomeric DNA complexes, and immune complex deposition in glomeruli. The 564Igi model confirmed this based on anti-dsDNA and plasma cell output. In vitro, loss of Bcl-6 prevented GC B cell expansion and accelerated plasma cell differentiation. In a competitive scenario in vivo, B cells harboring the genetic GC block contributed disproportionately to the plasma cell output. We identified the extrafollicular pathway as a key contributor to autoimmune progression. We propose that therapeutic targeting of low quality and poorly controlled extrafollicular responses could be a desirable strategy to curb autoreactivity, as it would leave intact the more stringently controlled and high-quality GC responses providing durable protection against infection.